ALIH AKSARA DAN ALIH BAHASA TEKS SEJARAH RINGKAS AULIYAULLAHUSSHALIHIN SYEKH BURHANUDDIN ULAKAN YANG MENGEMBANGKAN AGAMA ISLAM DI DAERAH MINANGKABAU VERSI IMAM MAULANA ABDUL MANAF AMIN AL-KHATIB - Dewi, Nova Sri; Hasanuddin WS, Hasanuddin WS; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2014)
This article was written to (1) describe of teks story about Brief History Auliyaullahusshalihin sheikh Burhanuddin Ulakan The Developing Regions of Islam In Minangkabau version Imam Maulana Abdul Manaf Amin Al-Khatib, (2) describe the translation of story about Brief History Auliyaullahusshalihin sheikh Burhanuddin Ulakan The Developing Regions of Islam In Minangkabau version Imam Maulana Abdul Manaf Amin Al-Khatib, (3) describe change language of story about Brief History Auliyaullahusshalihin sheikh Burhanuddin Ulakan The Developing Regions of Islam In Minangkabau version Imam Maulana Abdul Manaf Amin Al-Khatib. The objeck of this study were story about Brief History Auliyaullahusshalihin sheikh Burhanuddin Ulakan The Developing Regions of Islam In Minangkabau version Imam Maulana Abdul Manaf Amin Al-Khatib. The text was data processing by four step, is roundup of data, describe of the text, translation, and change language. The finding of the study is avalaible of text about Brief History Auliyaullahusshalihin sheikh Burhanuddin Ulakan The Developing Regions of Islam In Minangkabau version Imam Maulana Abdul Manaf Amin Al-Khatib in Latin script and Indonesian language and more words that indicate old language charactheristic.